Perlindungan Hukum Terhadap Anak Korban Eksploitasi Seksual Berdasarkan Hukum Islam - A. A Mas Stela Kurtika adi; Anak Agung Sagung Laksmi Dewi; Ni Made Sukuryati Karma (Jurnal Konstruksi Hukum, 2021)
A good nation's children are a reflection of good quality, so they need to be protected to get the authority to grow, develop, and obtain a prosperous life. But at this time the protection and welfare of children is still lacking, one of which is the issue of sexual exploitation of children so that it becomes a category of crimes against humanity that must be avoided and destroyed. The purpose of this study is to discuss the legal arrangements for child exploitation contained in Islamic law and criminal sanctions against perpetrators of child exploitation according to Islamic law. The method used is a normative legal method with a statutory and conceptual approach to problems. The results of the discussion state that exploitation is a form of effort carried out to carry out a deepening of the capacity contained in an object, whether it is in the form of natural resources or otherwise, in terms of the relevance of a group/many of people, the factors that cause exploitation of children, namely poverty, effects of social conditions, motivation workers to families. Criminal sanctions for exploitation of children are in Law number 35 of 2014 Article 14 paragraph (1), Article 81 paragraph (1) and Article 82.